Fcγ Receptor IIa (FCGR2A) Polymorphism Is Associated With Severe Respiratory Syncytial Virus Disease in Argentinian Infants - Holgado, María Pía; Raiden, Silvina; Sananez, Inés; Seery, Vanesa; De Lillo, Leonardo; Maldonado, Lucas L.; Kamenetzky, Laura; Geffner, Jorge; Arruvito, Lourdes (Frontiers in Cellular and Infection Microbiology, 2020)
Background Most patients with Respiratory Syncytial Virus (RSV) infection requiring hospitalization have no risk factors for severe disease. Genetic variation in the receptor for the Fc portion of IgG (FcγR) determines their affinity for IgG subclasses driving innate and adaptive antiviral immunity. We investigated the relationship between FcγRIIa-H131R polymorphism and RSV disease. Methods Blood samples were collected from 182 infants ≤24-month-old (50 uninfected, 114 RSV-infected with moderate course and 18 suffering severe disease). FcγRIIa-H131R SNP genotypic frequencies (HH, HR, RR) and anti-RSV IgG1, IgG2 and IgG3 levels were studied. Results Genotypic frequencies for FcγRIIa-H131R SNP were comparable between uninfected and RSV-infected infants. In contrast, we found a significant higher frequency of HH genotype in severe RSV-infected children compared to moderate patients. Among severe group, HH infants presented more factors associated to severity than HR or RR patients did. Furthermore, compared to moderate RSV-infected infants, severe patients showed higher levels of anti-RSV IgG1 and IgG3. Conclusions We found an association between an FcγRIIa (H131) polymorphism and severe RSV disease, which points towards a critical role for interactions between FcγRs and immune complexes in RSV pathogenesis. This genetic factor could also predict the worse outcome and identify those infants at risk during hospitalization.